Effect of Some Probiotics and Synbiotic Dietary Supplementation on Growth Performance and Some Health Parameters of Common Carp, Cyprinus Carpio (Journal of Pharmaceutical Negative Results, 2022)
The study was conducted to show the effect of using the prepared synbiotic and comparing it with the local Iraqi probiotic and the commercially imported synbiotic as a feed additive in the diets of common carp for the period of 70 days. 75 fingerlings with a starting weight of 11.15±.00 g, live mass of 55.94±1.5 g and an average length of 9.1 ± 1.5 cm were randomly distributed among five treatments (three replicates for each treatment and five fish for each replicate) and cultured in the closed rotating system. A standard diet was prepared and added to 0.1% each of the Iraqi probiotic (T2), commercial imported probiotic (T3), commercial import synbiotic (T4) and the synbiotic (T5) from lactic acid bacteria (Streptococcus themophilus and Lactococcus bulgaricus). The experimental diets were 3% of the body weight and the fish were weighed every 14 days. The results showed the superiority of the fifth treatment (T5) for the studied traits and the results indicated a significant difference (P<0.05), between them and the experiment’s parameters in growth criteria, which included a final weight rate of 130.48 g, weight gain of 73.65 g, daily growth rate of 1.05 g/day, specific growth rate of 1.19 g/day, condition factor of 1.69 and ration evaluation criteria that the amount of feed included 167.48 g, the feed conversion ratio 2.28. The best protein ratio was 18.28% and the lowest fat percentage was 4.22% in the chemical analysis of body components. Increasing the intestinal content of the total bacterial count and the counts of lactic acid bacteria (63.33×106 and 11×106) cfu/g, respectively, and improving the lipid profile in the blood serum, which included total cholesterol, triglycerides and both high- and low-density lipoproteins (117.81, 74.63, 56.96 and 45.92) mg/dL respectively.